EFEKTIVITAS GAME-BASED LEARNING BERBASIS GIMKIT SEBAGAI MODEL PENINGKATAN LITERASI PESERTA DIDIK SEKOLAH DASAR - Cahyaningrum Sasongko, Dian Anjani; Hermawan, Jody Setya; Perdana, Dayu Rika; Yulistia, Annisa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The background of this study is the low level of literacy skills, particularly in reading and the use of digital technology, among students, which stems from the suboptimal use of innovative and interactive teaching methods by educators. This study aims to evaluate whether a game-based learning approach using Gimkit in Pancasila education can significantly improve students’ literacy skills at SD Negeri 01 Metro Utara, Grade 5. In this study, the method applied was a quasi-experimental design using an unequal control group design. The total study population consisted of 75 students, with 51 students selected as the sample. Hypothesis testing was conducted using a simple linear regression formula, yielding a result of 0.00 < 0.05, which means H0 is rejected and Ha is accepted. Therefore, it can be concluded that the implementation of the Gimkit-based game-based learning model in Pancasila education has proven effective at SD Negeri 01 Metro Utara.